Srategi Menajemen Diklat Dalam Meningkatkan Kompetensi Tik Guru Paud di TK Pembina 2 Medan - Elya Siska Anggraini; Beatrix Marianta; Dinda Aulina Sinaga; Karina Dinda Adriani; Sulastri Diana Lumbantoruan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Teachers' information and communication technology (ICT) competency is a crucial factor in supporting innovative learning processes in early childhood education. However, some teachers still experience difficulties utilizing technology in their learning activities. This situation necessitates the need for effective education and training (diklat) management strategies to improve teachers' ICT competency. This research employed a qualitative approach with a case study conducted at Pembina 2 Kindergarten in Medan. Data were obtained through observation, interviews, and documentation, then analyzed using an interactive analysis model encompassing data reduction, data presentation, and conclusion drawing. The results indicate that the training implementation contributed to improving teachers' understanding of the use of technology in learning. However, the training implementation still faced obstacles such as differences in technology proficiency among teachers and limited opportunities to participate in training. To address these challenges, the school implemented a strategy of knowledge sharing and mentoring among teachers in the use of learning technology. A planned and sustainable training management strategy can improve teachers' ICT competency and support a more effective and innovative learning process.